PENGGUNAAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN MENULIS TEKS PUISI PADA PESERTA DIDIK - Hasriati; La Ode Adili; Amirudin Rahim (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
The purpose of this study was to describe the effectiveness of learning to write poetry texts using audio-visual media for class VIII students of SMP Negeri 1 Wadaga, West Muna Regency. This study is classified as a field research. The method used in this study is a quantitative descriptive method. The population in this study were all class VIII students of SMP Negeri 1 Wadaga. The sample in this study was 22 students of class VIII-3 of SMP Negeri 1 Wadaga. The instrument used to collect data in this study was the effectiveness of learning to write poetry texts using audio-visual media given to students in the form of a written test. Based on the results of data analysis, it can be concluded that student learning outcomes are classified as very effective because they reach an effectiveness level of 100%. Student activities in learning are classified as very effective because they reach an effectiveness level of 90%. Teacher activities in learning are classified as very effective because they reach an effectiveness level of 95%. Student responses can be said to be very effective because they reach an effectiveness level of 94.54%.